Application of Combined Median- Averaging Filters to Scintigraphic Image Processing - Grochulski, W.; Mitraszewski, P.; Penczek, P. (Nuklearmedizin - NuclearMedicine, 1985)
Statistical and deterministic properties of median filters are briefly discussed and their inherent advantages as a prospective tool in scintigraphic data processing are pointed out. The ability of median filters of suppressing impulse noise while the edge-like features of an image are preserved, is demonstrated on phantom data. The residual high-frequency noise remaining after median filtering can be subsequently reduced by standard smoothing procedures. A simple algorithm, made up of the superposition of a median and an averaging filter, is presented and shown to be a promising candidate in the quest for fast and easy-to-implement processing routine.